THE EXPERIENCE OF HOPANTENIC ACID APPLICATION IN THE SYRUP FOR THE CHILDREN, SUFFERING FROM EPILEPSY WITH COGNITIVE DISORDERS AND ATTENTION DEFICIT AND HYPERACTIVITY DISORDER - V.I. Guzeva; D.D. Korostovtsev; M.Yu. Fomina; V.V. Guzeva; O.V. Guzeva ("Paediatrician" Publishers LLC, 2007)
The search for nootropic medications, which don't aggravate the implications of the hyperactivity disorder and sleep disturbances, is an urgent issue in the children's neurology. For the purpose of pantohamium sirupus appraisal, the researchers examined 20 patient aged between 3 years old and 4 years 11 months old, suffering from epilepsy with cognitive disorders and attention deficit and hyperactivity disorder. All the patients underwent interviewing with the composite questionnaire, oddball tasks, mechanical memory tests (memorizing 3-4 words), dynamic memory tests (repeating 2 groups of words), colour test (for the children of 4 years old), as well as electroencephalography and by indications clinical and biochemical examination. After the course of panto hamium sirupus treatment the researchers discovered the general improvement of attention, mechanical and dynamic memory, anxiety reduction and compensation boost based on the colour test conducted among the children, suffering from epilepsy with attention deficit and hyperactivity disorder. Most patients showed the improvement indices of the EEG background rhythm structure and normalization of background zone differences. The analysis of the obtained results allowed the researchers to conclude that pantohamium sirupus was safe and efficient in the complex therapy among the children, suffering from epilepsy with cognitive disorders and attention deficit and hyperactivity disorder.Key words: hopantenic acid, pantohamium, epilepsy, attention deficit, hyperactivity, cognitive disorders.